PENERAPAN METODE SCAMPER DALAM MENGEMBANGKAN KEMAMPUAN PEMECAHAN MASALAH DITINJAU DARI MOTIVASI MAHASISWA PENDIDIKAN MATEMATIKA UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA - Tahir Tahir; Marniati Marniati (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2020)
This research is based on learning in tertiary institutions which requires more active, independent and creative learners. of the importance of using appropriate learning methods in mathematics learning at the university level. SCAMPER is a technique that can be used to spark creativity and help overcome challenges that might be encountered in the form of a list of general goals with ideas spurring questions. This research aims to develop students' problem solving skills using the SCAMPER method in terms of student motivation. The population in this study were all semester V students of mathematics education study programs, which were also the research samples. From the analysis of the data it was found that the SCAMPER method was better in developing students' problem solving abilities with an average increase of 0.52 compared to conventional methods with an average increase of 0.45. In addition there is a difference between improving students' problem solving abilities when viewed from their motivation. But there is no interaction between motivational factors and learning methods.